Ion transport in gel and gel–liquid systems for LiClO4-doped PMMA at the meso- and nanoscales. Issue 42 (18th October 2017) - Plett, Timothy; Thai, Mya Le; Cai, Josslyn; Vlassiouk, Ivan; Penner, Reginald M.; Siwy, Zuzanna S.
Abstract : Ionic transport in gel electrolytes at the nano- and mesoscales is explored experimentally using single pores. Abstract : Solid and gel electrolytes offer significant advantages for cycle stability and longevity in energy storage technologies. These advantages come with trade-offs such as reduced conductivity and ion mobility, which can impact power density in storage devices even at the nanoscale. Here we propose experiments aimed at exploring the ion transport properties of a hybrid electrolyte system of liquid and gel electrolytes with meso and nanoscale components. We focus on single pore systems featuring LiClO4 -propylene carbonate and LiClO4 -PMMA gel, which are model electrolytes for energy storage devices. We identified conditions at which the systems considered featured rectifying current–voltage curves, indicating a preferential direction of ion transport. The presented ion current rectification suggests different mechanisms arising from the unique hybrid system: (i) PMMA structure imposing selectivity in fully immersed systems and (ii) ionic selectivity linked to ion sourcing from media of different ionic mobility. These mechanisms were observed to interplay with ion transport properties linked to nanopore structure i.e. cylindrical and conical.